Labour market integration of foreign skilled workers in Canada and Germany : comparative findings from the healthcare sector - Annen, Silvia [Verfasser] (My University, 2019)
"The current occupation does not always match the training occupation. Education-job match relates to the professional field or to the qualification level of the tasks carried out in the current occupation. If an occupational change has taken place, i.e. if training and current occupation are not the same, occupation-specific knowledge and skills may be lost, and the risk for overqualification may thereby be higher. Focusing on the relationship between training and current occupation, this article investigates whether, and to which extent, vocational education and training can enable women and men to do a job adequately matched to their qualification level. This also applies after an occupational change has taken place. The analysis bases on data from the BIBB/BAuA Employment Survey 2018." (author's abstract; BIBB-Doku)
Keywords: P 1.5 Migranten; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; G 1.3.3.1 Qualifikationsverwertung; I 2.3.2 Nordamerika; Ausländischer Arbeitnehmer; Auslandsqualifikation; Anerkennung; Berufserfahrung; Qualifikationsverwertung; Berufliche Integration; Gesundheitswesen; Kanada; Bundesrepublik Deutschland